(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2025)
The aim of this study was to examine the impact of sustainability accounting on improving financial performance and enhancing social responsibility in selected Libyan commercial banks in the city of Sirte. The study employed the descriptive-analytical method, and its population consisted of all employees in Libyan commercial banks who are directly related to the subject of the research, totaling 250 individuals. A proportional stratified random sampling technique was used to ensure proper representation of the original population. A total of 168 questionnaires were distributed, of which 143 valid questionnaires were retrieved for analysis. The findings revealed a statistically significant impact of sustainability accounting on improving financial performance and enhancing social responsibility. Furthermore, the results indicated a statistically significant effect of sustainability accounting on increasing profitability, reducing indebtedness, and improving financial efficiency, in addition to its role in strengthening the economic, social, and environmental dimensions of social responsibility. The study recommends activating sustainability accounting practices through the development of sustainable financial policies, improving debt management, investing in training and technology, and supporting developmental, social, and environmental initiatives to achieve a balance between financial performance and sustainable development.